Inclusive Education Course for Guidance and Counselling Students - Pradnyandari Aulia Rahma; Tryastuti Irawati Belliny Manullang; Sunardi Sunardi; Aas Saomah (Journal of ICSAR, 2021)
Guidance and counseling program is a component of the school education program that requires close relationships with students as well as the ability to serve students well regardless of their background or condition. In the Guidance and Counselling Department at Universitas Pendidikan Indonesia, an inclusive education course is given to all students for one semester. Therefore, this study aimed to determine the effectiveness of inclusive education given in one semester for guidance and counseling students. This study used a survey method through Google Form, distributed to students who have studied inclusive education courses at the guidance and counseling department. The result showed that getting an inclusive education course had a positive impact on the student, 91% stated that the method was adequate and duration was sufficient. In addition, students learned more about the importance of inclusive education, which gave them a new perspective about students with special needs that would help them complement knowledge in their field after graduation. Students knew the challenges and opportunities they would experience after graduation. However, the lecture should be improved as the lecture was monotonous and focused more on textbooks and PowerPoint presentations. Besides, the lecturer had not been able to integrate the course with guidance and counseling. Further research with more comprehensive discussion and more respondents to provide more accurate and comprehensive results should be conducted in the future. This study was conducted online so that researchers could not identify respondents’ reactions when filling in the survey, so this can be considered.